Pengaruh Kualitas Produk Dan Pemasaran Konten Aplikasi Tiktok Terhadap Keputusan Pembelian Konsumen Skincare Skintific (Studi Kasus: Generasi Z Di Jakarta) - Prihadini, Diana; Sudinta, Heru; Frara, Elizabeth Monica (JAMBIS : Jurnal Administrasi Bisnis, 2023)
The rapid and continuous growth of technology has significantly impacted communication, shifting it into the digital realm where people access various information. This technological development has led to the emergence of online marketing, showcasing product quality through social media and influencing customers in making purchasing decisions. This research aims to understand and analyze the influence of product quality and content marketing of the TikTok application on consumer purchasing decisions of Skincare Skintific, with a case study on Generation Z in Jakarta. The research adopts a quantitative approach, utilizing purposive sampling with 100 respondents. Data collection is done through questionnaire observation. The research findings indicate that product quality (X1) influences purchasing decisions (Y) by 75.4%, with a calculated t-value of 5.680 > t-table 1.98472 and significance value of 0.00 < 0.05. Content Marketing (X2) influences purchasing decisions (Y) by 76%, with a calculated t-value of 5.957 > t-table 1.98472 and significance value of 0.00 < 0.05. Product quality (X1) and Content Marketing (X2) jointly (simultaneously) influence purchasing decisions (Y) by 81.8%, with the remaining 18.2% influenced by unexamined variables, supported by an F-value of 223.247 > F-table 3.09 and significance value of 0.00 < 0.05. In conclusion, both product quality and content marketing on TikTok significantly influence the purchasing decisions of Skincare Skintific consumers among Generation Z in Jakarta.